Adsorption of 2, 4-dichlorophenoxyacetic acid onto oil palm trunk-derived activated carbon: Isotherm and kinetic studies at acidic, ambient condition. (2022) - Mohd Noor Hazrin, Hanna Maizura; Lim, Adeline; Li, Claudia; Chew, Jiuan Jing; Sunarso, Jaka
Abstract: Adsorption represents an attractive method to remove pesticide from contaminated water given its relatively low cost and simple process. This work evaluates the adsorption isotherms and kinetics of 2, 4-dichlorophenoxyacetic acid (2, 4-D) onto oil palm trunk-derived activated carbon (OPT-AC). Batch adsorption was performed to determine the effects of pH, temperature, initial adsorbate concentration, and contact time. The highest removal efficiency was obtained at pH 2 due to the absence of electrostatic repulsion between the adsorbent and the adsorbate as indicated by the point of zero charge ( p H pzc ) of 4.8 for OPT-AC and a p K a of 2.73 for 2, 4-D. The adsorption isotherm data at 25, 35, and 45 °C and pH of 2 can be fitted better by the non-linear Langmuir model relative to the non-linear Freundlich model. Langmuir monolayer maximum adsorption capacity was found to be 420.43 mg g −1, which lies among the highest reported values for activated carbon materials used for 2, 4-D removal. Adsorption kinetic data at 35 °C and pH of 2, on the other hand, can be better correlated by pseudo-second order (PSO) kinetic model compared to pseudo-first order (PFO) model, which implies the more dominant presence of chemisorption relative to physisorption. The high adsorption uptake of 2, 4-D by OPT-AC highlights its potential as an attractive alternative to commercial AC particularly for medium to large scale 2, 4-D removal from acidic wastewater.